Beyond Borders: Mindol Qutuɣtu and His Early Approach to Combined Medical Practice - Tsetsenbaatar Gunsennyam; Batsaikhan Norov; Alimaa Tugjamba; Chimedragchaa Chimedtseren (Religions)
The spread of Tibetan Buddhism in Mongolia brought with it a wealth of Buddhist knowledge. Over time, Mongolian scholars and practitioners engaged with this knowledge and produced numerous works encompassing Buddhist learning, particularly in medicine. A prominent figure in this intellectual landscape is the Fourth Mindol Nomun Khan, Jambalchoijidanzanperenley (1789–1839), commonly known as Mindol Qutuɣtu (or Mindol Hutugtu). Despite being recognized for his remarkable contributions to the development of Mongolian medicine, considerable uncertainty has surrounded Mindol Qutuɣtu’s ethnic identity. This article aims to clarify Mindol Qutuɣtu’s ethnic origin and examine the broader medical context of his seminal work, The Treasury of All Precious Instructions (Man ngag rin chen ’byung gnas), highlighting the visionary concepts he presented. While the basis of Mindol Qutuɣtu’s work lies in Tibetan medicine, he boldly introduced treatment methodologies from other medical traditions, including Indian (Ayurvedic), Chinese, and European medicine, into the realm of Mongolian medicine. His insightful work reflects both intellectual ambition and practical occupation on increasing healing efficacy, as evidenced by his influential contributions to a combined and multicultural approach to medicine. Today, his innovative and inceptive contributions remain essential in understanding the historical development and current diverse character of Mongolian traditional medical practices.